Hipnokomunikasi Dalam Aplikasi Pasha (Pain Assessment, Stimulating And Healing Application) Dalam Menurunkan Nyeri Pasien Post Operasi - rezkiki, fitrianola; Kartika, Imelda Rahmayunia; Ceria, Nabila Puti (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2023)
Postoperative pain is the body’s reaction to tissue damage (ranging from skin incisions to damage from surgery), stretching or tightening of internal organs, and diseases (eg cancer, spinal diseases, etc). There are several pain management options in the PASHA (Pain Assessment, Stimulating and Healing Application) application to reduce the pain scale felt by patients, one of which is hypnocommunication. The purpose of this study was to find out how effective hypnocommunication on reducing pain of postoperative patients. This study used a quasy experimental design with a one-group pre-test and post-test approach by measuring the pain scale using the NRS (Numeric Rating Scales). The sample of this study was 30 postoperative patients in the surgical room who were selected by purposive sampling with several inclusion criteria.. The intervention was carried out using the PASHA application and the patient was listened hypnocommunication therapy for 15 minutes in 2 consecutive days The data were collected through computerization by using an dependent t-test. The results of the study showed that the average respondent’s pain intensity before being given hypnocommunication was 5.167 (moderate pain) and the average repondent’s pain intensity after being given hypnocommunication was 4, 00 (moderate pain). It can be conclude there was a significant effect of providing hypnocommunication based on the PASHA application in reducing postoperative patient pain (p value = 0.001). It is recommended to nurses especially in treating pain of postoperative patients by applying hypnocommunication as a non pharmacological pain therapy